DEVELOPMENT AND ADOPTION OF MANAGEMENT DECISIONS IN CHANGE MANAGEMENT (LITERATURE REVIEW) - Kenina, Diana S.; Levushkina, Svetlana V.; Svystunova, Inna G. (Nauka Krasnoi͡a︡rʹi͡a, 2022)
Dynamism and aggressive environmental factors leave no chance for organizations of all types of activities, except to follow modern trends and react flexibly by restructuring their activities and the activities of teams. Today, managers have a large set of tools and ready-made solutions for implementing changes, but we believe that a list of indicators is needed by which the sequences and methods of transformations will be determined. Undoubtedly, the institutional framework for making changes in organizations is important, the work contains a list of global organizations that provide both information and consulting and educational support. The process of reactions and adaptation to changes is quite complicated, as it encounters various obstacles in its path, and the decision-making procedure in such conditions is not simple either. The article decomposes the process of possible changes, taking into account risk factors and uncertainty, which allows identifying possible barriers and selecting appropriate methods of development and decision-making. The gamification method is considered as one of the relevant tools for preparing for changes, thanks to which it is possible to simulate new conditions and work out possible staff mistakes, in addition to reveal and develop the creative abilities of employees. Purpose the study of the features of the development and adoption of managerial decisions in change management. Methodology the article mainly used the method of theoretical analysis of the available scientific and theoretical base in the field of change management. Results: the most informative criteria, the need for changes in organizations and the algorithm of development and decision-making in the conditions of transformation of the organization are obtained. Practical implications it is advisable to apply the obtained results to both management theorists and practitioners in order to improve work in the field of change management.